Regulation of odd-numbered fatty acid content plays an important part in the metabolism of the hyperaccumulator Noccaea spp. adapted to oxidative stress - Pavlík, Milan; Zemanová, Veronika; Pavlíková, Daniela; Kyjaková, Pavlína; Hlavsa, Tomáš (Journal of plant physiology, 2017)
Relatively little is known about why odd-numbered fatty acids (OFAs) can be synthesized only by some plant species. We aimed at determining whether there is a relationship between the effects of Cd-induced oxidative stress on unsaturated fatty acids (USFAs) and their degradation products, especially OFAs. Plants with different ability to accumulate Cd - Noccaea praecox from Mežica, Slovenia (Me) and two ecotypes of Noccaea caerulescens from Ganges, France (Ga) and Redlschlag, Austria (Re) were cultivated in pot experiments. Only Me plants contained OFA 13:0, while all plants contained OFAs 15:0, 17:0 and 23:0 but in different proportions. Mutual correlations showed a significant effect of Cd contamination on the content of OFAs and USFAs in Me, a less pronounced effect in Re and the lowest one in Ga plants. The most significant correlation between the contents of USFAs and OFAs was also calculated for Me plants. The correlations between OFAs and USFAs indicate an active participation of OFA in FAs metabolism. Increased efficiency of utilization of the assimilated carbon via OFAs metabolism of Me plants in contrast to Re and Ga is also reflected in the increase of tolerance of Me plants to Cd toxicity in plant cells.
Keywords: Stress, Physiological; Senescence; mastné kyseliny; biodegradace; oxidační stres; kadmium; Fatty Acids; Cadmium; Phytoremediation; Oxidative Stress; Slovenia; Heavy metals; Thlaspi species; Austria; Francie; fyziologická adaptace; Ecotype; Fatty Acids, Unsaturated; fyziologický stres; Slovinsko; Brassicaceae; nenasycené mastné kyseliny; Adaptation, Physiological; France; Biodegradation, Environmental; Phylogenetic profiling of fatty acids; Environmental stress; ekotyp; Rakousko